Celebrating Adam Watkins First Birthday in Watkins' Backyard - Watkins, Howard::::::::: (1979)
Tony Correia, Dianne Shilton, Christine Watkins, Howard Watkins, Frances Kamp, Ruth Wall, Peggy Sanders, Laurie Leifer, Norma Herman, ??, John Olgesby, Mama Lupe, Joanna Cordova, David Brodie, Lucy Garcia William Leifer, Doug Broten, Janice Pearson, Stephanie Lieberman Guests seated under patio viewing televised video of Adam Watkins' birth